Pembuatan Bio-Oil Dari Kayu Cemara (Causarina Equisetifolal) Dengan Teknologi Pirolisis Menggunakan Katalis MO/NZA - Hasnul Bustaman; Syaiful Bahri; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bio-oil can be produced by pyrolisis of causarina wood with catalyst Mo/NZA. The purpose of this research was to produce bio-oil from causarina wood, determine the effect of theimpregnation percentage of Mo metal and ratio of Mo/NZA catalyst on the yield of bio-oil and determine the physical and chemical characteristics of bio-oil. Pyrolysis using 50 grams causarina wood, 500 ml silinap and Mo/NZA catalyst with variations of the impregnation percentage of Mo metal 0%, 0,5%, 1%, 1,5% and the variation ratio of Mo/NZAcatalyst 3% and 5% of the biomass with a stirring speed of 300 rpm and a temperature of 320ºC for 120 minutes. In this research, the highest yield on the variation of the impregnation percentage of metal 1,5% and the ratio of catalyst 5% of the biomass amounted to 66,79%. Characteristics of bio-oil obtained were density 1,012 gr/ml, viscosity 3,14 cP, acid number 75,48 mg NaOH/gr sample, and the flash point 52oC. The results of GC-MS analysis, the dominant chemical components inthe bio-oil were 2-propanone,1-hydroxy- with an area 51,55 % , 1,1’-bibicyclo(2.2.2)octyl-4- carboxylic acid with an area 14,77 % dan 2-Propanone with an area 0,8 %.Keywords: Bio-oil, Pyrolysis, Catalyst Mo/NZA, Causarina wood